Pengembangan Aplikasi Mobile Untuk Pengenalan Budaya Adat Dayak Ngaju - Evaristo, Juanito Da Silva; Abbad, Ikrimach (STMIK Banjarbaru, 2024)
The Introduction to Dayak Ngaju Cultural Customs Application is a digital platform that aims to introduce and document the cultural heritage and traditions of the Ngaju Dayak tribe. This application is designed to expand the general public's understanding of the rich culture, customs, arts, and beliefs held by the Dayak Ngaju tribe, one of the indigenous tribes in Indonesia. The purpose of making an application to introduce Dayak Ngaju cultural customs This application is a means to store, maintain, and perpetuate information about cultures that may be threatened with loss due to modernization and changing times. Methods used in applications using the RAD method This method places more emphasis on prototype development, intensive interaction with users, and rapid iteration to speed up application development time. The use of RAD method in the development of applications for the introduction of Dayak Ngaju culture. As a result of the development of this application, the general public, especially the younger generation, can gain deeper knowledge about the richness of Dayak Ngaju culture. This application can be an easily accessible educational resource to expand understanding of the culture.Keywords: Dayak Tribe; Dayak Ngaju Culture; Mobile Technology; Mobile Application; Central Borneo.Â AbstrakAplikasi Pengenalan Adat Kebudayaan Dayak Ngaju adalah sebuah platform digital yang bertujuan untuk memperkenalkan serta mendokumentasikan warisan budaya dan tradisi yang dimiliki oleh suku Dayak Ngaju. Aplikasi ini dirancang untuk memperluas pemahaman masyarakat umum tentang kekayaan budaya, adat istiadat, seni, dan kepercayaan yang dimiliki oleh suku Dayak Ngaju, salah satu suku asli di Indonesia. Tujuan dari pembuatan aplikasi pengenalan adat kebudayaan Dayak Ngaju Aplikasi ini menjadi sarana untuk menyimpan, memelihara, dan mengabadikan informasi tentang budaya yang mungkin terancam hilang akibat modernisasi dan perubahan zaman. Metode yang digunakan dalam aplikasi menggunakan metode RAD Metode ini lebih menekankan pada pengembangan prototipe, interaksi yang intensif dengan pengguna, dan iterasi yang cepat untuk mempercepat waktu pengembangan aplikasi. Penggunaan metode RAD dalam pengembangan aplikasi pengenalan kebudayaan Dayak Ngaju Hasil dari pengembangan aplikasi ini masyarakat umum khususnya generasi muda, dapat memperoleh pengetahuan yang lebih dalam tentang kekayaan budaya Dayak Ngaju. Aplikasi ini dapat menjadi sumber pendidikan yang mudah diakses untuk memperluas pemahaman tentang kebudayaan tersebut.Â